Comparison of different drying technologies for green tea: Changes in color, non-volatile and volatile compounds - Nannan Li; Zhengying Yao; Jingming Ning; Lijun Sun; Qunying Lin; Xiaoyan Zhu; Cuihong Li; Xiaohe Zheng; Jinghong Jin (Food Chemistry: X)
Drying technology plays a pivotal role in tea processing. Herein, the differences in color, non-volatile, and volatile components of green tea under various drying methods were investigated. The results indicated that vacuum freeze-microwave increased the L* and b* values, and decreased the a* values of tea leaves. Moreover, vacuum freeze-microwave drying resulted in higher polyphenol content than the other three drying methods although there was no significant difference. A total of 43 volatile compounds were identified. Of these, 2-propanone, ethanol(D), ethanol(M), ethyl acetate(M), 2-methyl-1-butanol, and 2-methylthiophene were found to play an important role in the above discrimination (VIP >1.5). Dry extraction showed a higher content of volatile components than wet extraction. Regardless of the extraction conditions, vacuum freeze-microwave drying exhibited a stronger signal intensity and more volatile components than other drying methods. This study provides a reference for analyzing the quality differences of green tea by different drying methods.